Cyber security awareness training (SecurityGuts) - Ramli, Fatin Najwa; Mohd Fauzi, Nur Alya Nadirah; Talib, Shuhaili (KICT Publishing, 2024)
This project involves designing a module of cyber security awareness training (SecurityGuts) systems distinguished as an e-learning interaction application to educate users. The main objective of developing this ‘SecurityGuts’ application is to help users gain knowledge about scams and be aware of the scammer’s modus operandi in a fun and interactive way. This application is also to spread more awareness of the different types of scams and how to protect yourself from being scammed in hopes of decreasing the number of scam victims in Malaysia. SecurityGuts will be able to generate some quizzes to test the player's knowledge of scams after they explore the scam player's knowledge of scams after they explore the scam storylines that we have designed inside the gameplay. The application is developed using GameMaker 8.1.